Internacjonalizacja przedsiębiorstw – istota budowania konkurencyjności w dobie globalizacji korporacyjnej - Rosińska-Bukowska, Magdalena (Ekonomia Międzynarodowa, 2014)
The purpose of this article is to analyze the changes in the strategies of the internationalization of enterprises as a result of the evolution the global economy. An attempt is made to assess the impact of the progressive stages of the process of globalization on the models of functioning of enterprises, especially the rules of competitiveness building. The article is divided into four parts. The first part is an analysis of the evolution of the globalization processes. The second part refers to the impact of changes in the globalization process for businesses. The third part shows the implications of the current phase of globalization for the competitiveness system. The last part is an attempt to explain the methods of the implementation of these challenges using selected corporations as examples (Volkswagen, Siemens, British Petroleum).